Microstructural correlates of 3D steady‐state inhomogeneous magnetization transfer (ihMT) in the human brain white matter assessed by myelin water imaging and diffusion tensor imaging. Issue 6 (29th April 2018) - Ercan, Ece; Varma, Gopal; Mädler, Burkhard; Dimitrov, Ivan E.; Pinho, Marco C.; Xi, Yin; Wagner, Benjamin C.; Davenport, Elizabeth M.; Maldjian, Joseph A.; Alsop, David C.; Lenkinski, Robert E.; Vinogradov, Elena
Abstract : Purpose: To compare the recently introduced inhomogeneous magnetization transfer (ihMT) technique with more established MRI techniques including myelin water imaging (MWI) and diffusion tensor imaging (DTI), and to evaluate the microstructural attributes correlating with this new contrast method in the human brain white matter. Methods: Eight adult healthy volunteers underwent T1 ‐weighted, ihMT, MWI, and DTI imaging on a 3T human scanner. The ihMT ratio (ihMTR), myelin water fraction (MWF), fractional anisotropy (FA), radial diffusivity (RD), axial diffusivity (AD), and mean diffusivity (MD) values were calculated from different white matter tracts. The angle ( θ ) between the directions of the principal eigenvector, as measured by DTI, and the main magnetic field was calculated for all voxels from various fiber tracts. The ihMTR was correlated with MWF and DTI metrics. Results: A strong correlation was found between ihMTR and MWF (ρ = 0.77, P  < 0.0001). This was followed by moderate to weak correlations between ihMTR and DTI metrics: RD (ρ = −0.30, P  < 0.0001), FA (ρ = 0.20, P  < 0.0001), MD (ρ = −0.19, P  < 0.0001), AD (ρ = 0.02, P  < 0.0001). A strong correlation was found between ihMTR and θ (ρ = −0.541, P  < 0.0001). Conclusion: The strong correlation with myelin water imaging and its low coefficient of variation suggest that ihMT has the potential to become a new structural imaging marker of myelin. The substantial orientational dependence of ihMT should be taken into account when evaluating and quantitatively interpreting ihMT results.